ANEMIA IN YOUNG WOMEN IN THE CITY OF SOUTH TANGERANG IN 2023 - Ari Retno Setiyawaty; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Background: A health problem in adolescents that is still happening today is anemia. The problem of anemia in young women needs further treatment because young women are prospective mothers who will give birth to children as the successor to the nation. Purposes: The study aimed to describe the incidence of anemia and the recipients of blood-added tablets for young women in the city of South Tangerang. Methods: This research was conducted using descriptive research. The population of this study was young women who had been screened for Hemoglobin (Hb). From January to May 2023 in all junior high schools/equivalent grades 7,8,9 and high school/equivalent grades 10,11,12 in the city of South Tangerang there were 46,624 people. The data were obtained from the Hb screening report from the South Tangerang City Health Office and were analyzed univariately in the form of a frequency distribution. Results: The results showed that 15,015 girls (32.20%) experienced anemia with mild anemia at 54.41%, moderate anemia at 40.39%, and severe anemia at 5.20%. The highest percentage of anemia was in grade 9 reaching 37.56% and the highest prevalence of anemia for young women was in the Setu sub-district of 40.27%. For blood-added tablet recipients for young women in South Tangerang City, the rate has reached 67.63% of the target of 68%. Conclusions: This study concludes that the incidence of anemia in female adolescents is still high, exceeding the national target and the proportion of female adolescents receiving iron tablets is good. Collaboration between various parties is needed to reduce the prevalence of anemia among school girls' parents, regional officials from the health office, the education and culture office, and the Ministry of Religion of the city of South Tangerang regarding nutritional action activities and monitoring and evaluation of consumption of blood-added tablets in young women.